Trastuzumab- and Fab′ fragment-modified curcumin PEG-PLGA nanoparticles: preparation and evaluation in vitro and in vivo - Duan D; Wang A; Ni L; Zhang L; Yan X; Jiang Y; Mu H; Wu Z; Sun K; Li Y (International Journal of Nanomedicine, 2018)
Dongyu Duan,1,* Aiping Wang,1,* Ling Ni,2 Liping Zhang,1 Xiuju Yan,1 Ying Jiang,1 Hongjie Mu,1 Zimei Wu,1 Kaoxiang Sun,1 Youxin Li1,2 1School of Pharmacy, Collaborative Innovation Center of Advanced Drug Delivery System and Biotech Drugs in Universities of Shandong, Key Laboratory of Molecular Pharmacology and Drug Evaluation (Yantai University), Ministry of Education, Yantai University, Yantai, People’s Republic of China; 2State Key Laboratory of Long Acting and Targeting Drug Delivery System, Shandong Luye Pharmaceutical Co., Ltd, Yantai, People’s Republic of China *These authors contributed equally to this work Introduction: Nanoparticles (NPs) modified with bio-ligands represent a promising strategy for active targeted drug delivery to tumour. However, many targeted ligands, such as trastuzumab (TMAB), have high molecular weight, limiting their application for targeting. In this study, we prepared Fab’ (antigen-binding fragments cut from TMAB)-modified NPs (Fab'-NPs) with curcumin (Cur) as a model drug for more effective targeting of human epidermal growth factor receptor 2 (HER2/ErbB2/Neu), which is overexpressed on breast cancer cells. Material and methods: The release kinetics was conducted by dialysis bags. The ability to kill HER2-overexpressing BT-474 cells of Fab'-Cur-NPs compared with TMAB-Cur-NPs was conducted by cytotoxicity experiments. Qualitative and quantitative cell uptake studies using coumarin-6 (fluorescent probe)-loaded NPs were performed by fluorescence microscopy and flow cytometry. Pharmacokinetics and biodistribution experiments in vivo were assessed by liquid chromatography–tandem mass spectrometry (LC-MS/MS).Results: The release kinetics showed that both Fab'-Cur-NPs and TMAB-Cur-NPs provided continuous, slow release of curcumin for 72 h, with no significant difference. In vitro cytotoxicity experiments showed that Fab'-Cur-NPs manifested prominent ability to kill HER2-overexpressing BT-474 cells compared with TMAB-Cur-NPs. Qualitative and quantitative cell uptake studies indicated that the accumulation of Fab'-NPs was greater than that of TMAB-NPs in BT-474 (HER2+) cells; However, there was no significant difference in MDA-MB-231 (HER2-) cells. Pharmacokinetics and biodistribution experiments in vivo demonstrated that the half-life (t1/2) and area under the blood concentration-time curve (AUC0-t) of Fab'-Cur-NPs increased 5.30-fold and 1.76-fold relative to those of TMAB-Cur-NPs, respectively. Furthermore, the tumor accumulation of Fab'-Cur-NPs was higher than that of TMAB-Cur-NPs. Conclusion: Fab' fragment has greater capacity than the intact antibody to achieve tumor targeting through NP-based delivery. Keywords: trastuzumab-modified curcumin nanoparticles, Fab'-modified curcumin nanoparticles, pharmacokinetics, biodistribution, tumour targeting, breast cancer